DESAIN PANDU GELOMBANG PARALEL TERISOLASI DENGAN METHOD OF LINES - Syahriar, ary (Badan Pengkajian dan Penerapan Teknologi, 2006)
Optical directional couplers are fundamental building components for the design ofoptical circuits. The proper treatment of a device that couples the guided modes ofa waveguide with the radiation in free space is particularly difficult because of thecontinuum nature of the radiating modes. The desire of high-density integrationposes additional problems due to the fact that the simplest used couplingstructures need to be quite large. In order to reduce the size of the device we studynon-periodic structures based on air gap isolated directional couplers, for whichadditional degrees of freedom are available. The analysis of this type of structuresrequires a rigorous method for the solution of the field equations. We employ themethod of lines for the computation of such coupler characteristics.